2020
DOI: 10.7717/peerj.9255
|View full text |Cite
|
Sign up to set email alerts
|

Insights on early mutational events in SARS-CoV-2 virus reveal founder effects across geographical regions

Abstract: Here we aim to describe early mutational events across samples from publicly available SARS-CoV-2 sequences from the sequence read archive and GenBank repositories. Up until 27 March 2020, we downloaded 50 illumina datasets, mostly from China, USA (WA State) and Australia (VIC). A total of 30 datasets (60%) contain at least a single founder mutation and most of the variants are missense (over 63%). Five-point mutations with clonal (founder) effect were found in USA next-generation sequencing samples. Sequencin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 33 publications
4
28
0
Order By: Relevance
“…The founder effect, as a reason for genetic diversification, has been reported in many viruses and pathogens [55][56][57][58] including SARS-CoV [44], and, in HIV, has been an immense source of polymorphisms and evolution [55]. In a study evaluating the distribution of mutations in SARS-CoV-2 genomes, the clonal nature of mutations in different geographical regions was detected, leading to the assignment of the founder effect as the cause [59]. In the initial phases of endemic viral infections, viruses are under a constant selection pressure and certain lineages can eventually face extinction because of the competition with their more reproductively capable counterparts.…”
Section: Genomic Stability Estimation Of Sars-cov-2 Orf8mentioning
confidence: 99%
“…The founder effect, as a reason for genetic diversification, has been reported in many viruses and pathogens [55][56][57][58] including SARS-CoV [44], and, in HIV, has been an immense source of polymorphisms and evolution [55]. In a study evaluating the distribution of mutations in SARS-CoV-2 genomes, the clonal nature of mutations in different geographical regions was detected, leading to the assignment of the founder effect as the cause [59]. In the initial phases of endemic viral infections, viruses are under a constant selection pressure and certain lineages can eventually face extinction because of the competition with their more reproductively capable counterparts.…”
Section: Genomic Stability Estimation Of Sars-cov-2 Orf8mentioning
confidence: 99%
“…While the founder effect - whereby a small number of strains establish a new population - is a possible explanation for the increasing prevalence of the G614 variant 6 , accumulating evidence points to an evolutionary fitness advantage conferred on SARS-CoV-2 by this mutation. First, sequence analysis has revealed that the D614 variant was well established within several populations before the arrival of the G614 variant 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Although a vaccine for COVID-19 would be an optimal solution, the prospects for a safe and effective vaccine are murky at best and probably not a viable option in the next two years due to mutational variation of the virus and potential vaccine enhancement of viral infection. 8,9 Herd immunity to SARS-CoV-2 also may be difficult to achieve because the infection rate is too low. 10,11 Therefore, an alternate prevention strategy is needed when social distancing is phased out during economic recovery.…”
Section: Introductionmentioning
confidence: 99%